How we invented the airplane : an illustrated history - Wright, Orville, 1871-1948.; Kelly, Fred C. (Fred Charters), 1882-1959. (New York : Dover Publications, 1988)
"It was the realization of a dream as old as mankind. On December 17, 1903, a gusty winter day off the sand at Kitty Hawk (actually Kill Devil Hills), North Carolina, two bicycle mechanics from Dayton, Ohio achieved the first sustained, powered, heavier-than-air flight in a machine of their own design and construction. This book offers a concise and fascinating history of that remarkable accomplishment, much of it in the words of the inventors themselves...The achievement of the Wright brothers is placed in historical context in the absorbing and informative introduction to this volume, written by Fred C. Kelly, author of two standard works on the Wrights. Mr. Kelly has also written an illuminating commentary, including fascinating anecdotes about the Wrights, their personalities and later aspects of their career. As an added bonus, a lively popular account of the Wrights' success, written in 1908 by both brothers, has been included in an Appendix." --Excerpted and rearranged from back of book.
Introduction / by Fred C. Kelly -- Photographs, 1897-ca. 1900 -- How we invented the airplane / by Orville Wright -- Photographs, 1900-1903 -- After the first flights / by Orville Wright -- Photographs, 1904-1905 -- After Kitty Hawk: A brief résumé / by Fred C. Kelly -- Photographs, 1908-1940 -- Appendix to the Dover Edition: The Wright Brothers' Aëroplane / by Orville and Wilbur Wright.
""An unabridged, greatly enlarged republication of the work first published by the David McKay Company, Inc., New York, 1953 (incorporating a text written in 1920)""--T.p. verso.
Bibliography: p. vi.
Keywords: Wright, Orville, -- 1871-1948.; Wright, Wilbur, -- 1867-1912.; Airplanes